2023
DOI: 10.1002/alz.13040
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Montreal Cognitive Assessment tool for detecting mild cognitive impairment: A systematic review and meta‐analysis

Abstract: INTRODUCTION: This systematic review evaluates the accuracy of the Montreal Cognitive Assessment (MoCA) for detecting mild cognitive impairment (MCI). METHODS: We searched MEDLINE, PSYCInfo, EMBASE, and Cochrane CENTRAL for studies comparing the MoCA with validated diagnostic criteria to identify MCI in general practice. Screening, data extraction, and risk of bias assessment were performed independently, in duplicate. Pooled sensitivity and specificity for MoCA cutoffs were estimated using bivariate meta-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Although, the most commonly used cut-off of MoCA for MCI in the general population is 26 (score < 26 abnormal), there are studies which have found that this widely recommended cut-off leads to an inflated rate of false positives, (particularly in the elderly and people with lower education), and the cut-off score of 23 yields the best diagnostic accuracy [ 12 ]. A recently published systematic review evaluating the accuracy of MoCA for detecting mild cognitive impairment in the general population (13 studies, 2158 participants, 44% with MCI, mean age 72 years, mean education 13.5 years, race 93.4% Caucasian) also supports a lower cut-off [ 21 ]. In this meta-analysis, sensitivity and specificity were 73.5% and 91.3% respectively at cut-off < 23, while 93.7% and 58.8%, respectively, at cut-off < 26.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the most commonly used cut-off of MoCA for MCI in the general population is 26 (score < 26 abnormal), there are studies which have found that this widely recommended cut-off leads to an inflated rate of false positives, (particularly in the elderly and people with lower education), and the cut-off score of 23 yields the best diagnostic accuracy [ 12 ]. A recently published systematic review evaluating the accuracy of MoCA for detecting mild cognitive impairment in the general population (13 studies, 2158 participants, 44% with MCI, mean age 72 years, mean education 13.5 years, race 93.4% Caucasian) also supports a lower cut-off [ 21 ]. In this meta-analysis, sensitivity and specificity were 73.5% and 91.3% respectively at cut-off < 23, while 93.7% and 58.8%, respectively, at cut-off < 26.…”
Section: Discussionmentioning
confidence: 99%
“…The MoCA Full was selected due to its high sensitivity and specificity profile; reliability across multiple language, culture, and sensory needs; and validity when administered by trained non‐clinicians 11 , 12 , 13 compared to other less sensitive or culturally specific screening tools (e.g., 3MS, Eight‐Item Informant Interview to Differentiate Aging and Dementia [AD8], Short Portable Mental Status Questionnaire [SPMSQ]). CASS staff and associated researchers underwent MoCA training and certification.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, older participants completed the Montreal Cognitive Assessment (MOCA) to screen for any mild cognitive impairment. All older participants were above the threshold (MOCA Score ≥ 23) indicating no mild cognitive impairment 84 , 85 .
Figure 5 Behavioral tasks.
…”
Section: Methodsmentioning
confidence: 99%